Expansão de negócios da vitalife indústria de cosméticos com foco na comercialização de protetores solares populares na região nordeste do Brasil - Silva, Celso Flávio da (2020)
Introduction: This text describes the study carried out by Vitalife Indústria de Cosméticos to expand the commercialization of its line of sunscreens to the northeast of Brazil through the pharmaceutical retail (pharmacies and drugstores). Methodology Used: Followed the method of solving problems and taking advantage of opportunities proposed by Marcondes, Miguel, Franklin and Perez (2017). Investigated Context: The sunscreen market has grown at expressive rates in the last two decades in Brazil, whether due to the population's greater purchasing power or changes in consumer behavior. Particularly in the Northeast of Brazil, given its climatic and cultural characteristics and the population size, in addition to the absence of large local manufacturers, there are signs of potential sales of sunscreens and business opportunities for Vitalife. Diagnosis of the Situation: It started from the analysis of scenarios and trends in the competitive environment, such as the current and potential size of the Northeast market for sunscreens, as well as the performance strategy and positioning of the main competitors. Next, it sought to understand the modus operandi of representatives and distributors operating in the region, as well as their expectations and requirements, with the aim of formulating strategies to overcome barriers to entry and place products at points of sale. Proposed Intervention: The diagnosis made led to the design of a business model to create value for the various stakeholders, such as representatives, distributors, pharmacies and the final customer. The model evolved due to the more precise definition of the operation with the retail channels, integration of the production and logistics structure and analysis of financial viability and risks. Results Obtained: Business is growing at an accelerated pace, even in a time of pandemic, with partnerships already established with four distributors and the hiring of five local sales representatives. In addition, the first batches of sales to distributors and retailers have already occurred, including the replacement of merchandise in both cases, and the results signal in order to meet the company's expectations. Technological, Economic and Social Impact: This project has proven to be sustainable and in line with strategic objectives, and can provide a significant increase in the company's global revenue in the medium term. It can also enhance partnerships with investors, a strategy under analysis for the company's accelerated expansion. This increases the potential impact and relevance of the project in the economic dimension, but also technological (investment of capital for Research and Development) and even social (generation of jobs in the region).